Influence of Personality Type, Teamwork and Communication on Employee Performance at PT. General Takaful Insurance - Shahnaz Meutia Andrapuri; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to understand and analyze the effect of personality type, teamwork and communication on employee performance at PT. General Takaful Insurance. Sources of data in this study using primary data in the form of a questionnaire, this research data was given to 80 employees of PT. General Takaful Insurance. Sampling for this study used the saturated sampling method. The data analysis technique in this study is multiple linear regression and hypothesis testing (t-test) which is processed with SPSS 28 to test the coefficient of determination. The results of the study concluded that personality type, teamwork and communication have a positive, and significant effect on the performance of employees of PT. General Takaful Insurance.